2016
DOI: 10.3390/nu8120792
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Beta-Glucan Consumption (Saccharomyces cerevisiae) Improve the Metabolic Profile and Reduce the Atherogenic Index in Type 2 Diabetic Rats (HFD/STZ)

Abstract: Physical activity and the ingestion of dietary fiber are non-drug alternatives commonly used as adjuvants to glycemic control in diabetic individuals. Among these fibers, we can highlight beta-glucans. However, few studies have compared isolated and synergic effects of physical exercise and beta-glucan ingestion, especially in type 2 diabetic rats. Therefore, we evaluated the effects beta-glucan (Saccharomyces cerevisiae) consumption, associated or not to exercise, on metabolic parameters of diabetic Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
(70 reference statements)
0
9
0
1
Order By: Relevance
“…It comprises a group of β-D-glucose polysaccharides that are naturally occurring in the cell walls of bacteria after fermentation [21]. Experimental evidence has suggested that the consumption of beta-glucan from Saccharomyces cerevisiae could decrease blood glucose levels, lipid profile, and plasma atherogenic index in type 2 diabetic rats [60]. In addition, beta-glucan from oats ameliorated insulin resistance by enhancing hepatic glucose kinase activity [61].…”
Section: Discussionmentioning
confidence: 99%
“…It comprises a group of β-D-glucose polysaccharides that are naturally occurring in the cell walls of bacteria after fermentation [21]. Experimental evidence has suggested that the consumption of beta-glucan from Saccharomyces cerevisiae could decrease blood glucose levels, lipid profile, and plasma atherogenic index in type 2 diabetic rats [60]. In addition, beta-glucan from oats ameliorated insulin resistance by enhancing hepatic glucose kinase activity [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of islet β cell damage is dose-dependent ( 9 ). Following investigation of STZ dosage, 35 mg/kg has been identified as the optimal dosage of STZ to induce DM ( 10 , 11 ). Furthermore, increased doses of STZ have been associated with increased mortality in animals ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 ). The decrease of sugars could be ascribed to the delay and decrease in starch metabolism and carbohydrate absorption due to the action of BG (Andrade et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%